Local students vs international students perception towards Malaysian Library / Nurul Shazwani Abdul Aziz, Nurul Aishah Samin and Nurul Amirah Md Suhaimi - Abdul Aziz, Nurul Shazwani; Samin, Nurul Aishah; Md Suhaimi, Nurul Amirah (Faculty of Information Management, 2015)
In this article is discussed about the perception of those University students or how their perceptions to the academic library in their place which is in Malaysia. The comparison between the local students and the foreign students towards the library and how about their perception about the Malaysia library especially to the University which are IPTS and also IPTA library in Malaysia. The University libraries that were compared are UKM library which is Tun Sri Lanang Library and also University Malaya Library. In this article also shows about the International library which is the National Library of Korea.